God/Inspector “What is Hidden, Does Appear”: A Comparative Analysis of All-Seeing and Panopticon in Hymns for Trial Service and Bentham’s Vision of the Chapel - Wigorts Yngvesson, Susanne (Surveillance & Society, 2026)
This article explores the interplay between theological and utilitarian conceptions of omniscience and moral accountability through a comparative analysis of hymns from Swedish trial services (1686–1989) and Jeremy Bentham’s writings on surveillance architecture, particularly the chapel, examining how they illuminate contrasting frameworks for transforming human behavior under an omniscient gaze. While Lutheran hymns depict God’s omniscience as a transcendent, relational presence fostering repentance and spiritual renewal through divine grace, Bentham’s panopticon reimagines omniscience as a secular mechanism of behavioral regulation, achieved through perpetual surveillance. The analysis identifies thematic as well as social parallels—such as the transformative impact of observation and the role of moral reform—while highlighting key divergences. Hymns emphasize voluntary spiritual transformation anchored in divine mercy, whereas the panopticon enforces conformity through external pressure and institutional control. Theological reflections on omniscience, omnipresence, and justice in the hymns underscore a relational and redemptive paradigm, in contrast to the panopticon’s utilitarian focus on societal order and efficiency. This study contributes to previous research and the interdisciplinary discourse on surveillance, ethics, and religion, revealing how theological and secular paradigms of observation shape divergent understandings of justice, moral accountability, and human transformation.